ASOSIASI FUNGI MIKORIZA ARBUSKULA PADA TANAMAN MANGROVE DI DESA PASIR KECAMATAN MEMPAWAH HILIR KABUPATEN MEMPAWAH - Ramadhani, Fety Fitri; Ekamawanti, Hanna Artuti; Anwari, M Sofwan (JURNAL HUTAN LESTARI, 2019)
This research was aimed at discovering the types of Arbuscular Mycorrhizal Fungi (AMF) associated with mangrove plants. The research was conducted in Pasir Village, Mempawah Hilir District, Mempawah Regency, and the Silvicultural Laboratory of Forestry Faculty, Tanjungpura University Pontianak for one month. The samples collection of soil and root done survey method used purposive sampling technique. The primary data were the number of spores, genus of AMF, and AMF infection on root samples. While the secondary data were pH, air temperature, soil temperature, humidity, diameter, and height. The results showed that there were 7 species of Glomus spp. and mangrove plant (Avicennia marina, Bruguiera cylindra, Rhizophora stylosa) with AMF spore density of 247 spores /100 gr soil and level of root infection percentage from low class (class 2) up to medium class (class 3). Keywords: arbuscular mycorrhizal fungi (AMF), association, mangroves.